The Potential Anti-remodeling Effect of Paroxetine After Myocardial Infarction May Be Blunted by Beta-Blockers - Iborra-Egea, Oriol; Aimo, Alberto; Martini, Nicola; Galvez-Monton, Carolina; Burchielli, Silvia; Panichella, Giorgia; Passino, Claudio; Emdin, Michele; Bayes-Genis, Antoni (Frontiers in Cardiovascular Medicine, 2022)
Background: Left ventricular (LV) remodeling consists in maladaptive changes in cardiac geometry and function following an insult such as ST-segment elevation myocardial infarction (STEMI). Interventions able to prevent LV remodeling after a STEMI are expected to improve the outcome of this condition. Paroxetine has inhibitory effects on GRK2, also known as beta-adrenergic receptor kinase 1 (ADRBK1). This drug does not yield beneficial effects on LV remodeling in patients with STEMI and LV ejection fraction ≤45%. Methods: We compared the molecular effects of paroxetine and drugs for neurohormonal antagonism (beta-blockers, angiotensin converting enzyme inhibitors/angiotensin receptor blockers, mineralocorticoid receptor antagonists), using a bioinformatic approach integrating transcriptomic data in a swine model of post-MI and available evidence from the literature and massive public databases. Results: Among standard therapies for MI, beta-blockers are the only ones acting directly upon GKR2, but the mechanism of action overlaps with angiotensin-converting enzyme inhibitors/angiotensin receptor blockers with respect to the AT2R-mediated anti-hypertensive response. Moreover, Beta-blockers could also drive anti-fibrotic and anti-inflammatory effects through regulation of myocyte-specific enhancer factors, endothelins and chemokines. Conclusions: The additive benefit of paroxetine on the background of the standard therapy for STEMI, which includes beta-blockers, is expected to be limited. Nonetheless, paroxetine becomes particularly interesting when a beta-blocker is contraindicated (for example, in hypotensive individuals) or poorly tolerated.